2013
DOI: 10.1074/jbc.m113.516385
|View full text |Cite
|
Sign up to set email alerts
|

WhiB7, an Fe-S-dependent Transcription Factor That Activates Species-specific Repertoires of Drug Resistance Determinants in Actinobacteria

Abstract: Background: WhiB7 is essential for antibiotic resistance in M. tuberculosis. Results: WhiB7 requires conserved residues, including a redox-sensitive center and DNA-binding motif, to coordinate transcription of species-specific drug resistance genes in diverse Actinobacteria. Conclusion: WhiB7 activates species-specific drug resistance genes in Actinobacteria. Significance: Understanding WhiB7 activity may allow the development of drugs that sensitize bacteria to antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 81 publications
1
56
0
Order By: Relevance
“…While previous work found that Lsr2 regulates expression of the drug efflux pump IniBAC (Colangeli et al 2005, 2007), more recent studies suggested that Lsr2 also protects M. tuberculosis from oxidative stress (Bartek et al 2014; Colangeli et al 2009). WhiB7 is a MDR transcription regulator exclusively found in Actinobacteria including mycobacteria (Morris et al 2005; Ramon-Garcia et al 2013). Deletion of whiB7 leads to increased sensitivity to multiple antibiotics whereas overexpression results in enhanced resistance (Morris et al 2005).…”
Section: Bactericidal Activity Of Drugs and Oxidative Stress In Mycobmentioning
confidence: 99%
“…While previous work found that Lsr2 regulates expression of the drug efflux pump IniBAC (Colangeli et al 2005, 2007), more recent studies suggested that Lsr2 also protects M. tuberculosis from oxidative stress (Bartek et al 2014; Colangeli et al 2009). WhiB7 is a MDR transcription regulator exclusively found in Actinobacteria including mycobacteria (Morris et al 2005; Ramon-Garcia et al 2013). Deletion of whiB7 leads to increased sensitivity to multiple antibiotics whereas overexpression results in enhanced resistance (Morris et al 2005).…”
Section: Bactericidal Activity Of Drugs and Oxidative Stress In Mycobmentioning
confidence: 99%
“…WhiB7 and its orthologue, WblC, control innate multi-drug resistance in Mycobacteria and Streptomyces respectively (Morris et al, 2005;Ramon-Garcia et al, 2013). There is no obvious orthologue in Corynebacteria (Table 2 and Fig.…”
Section: Class V (Whib7/wblc)mentioning
confidence: 99%
“…One of the best studied regulators of this reprogramming circuit is WhiB7, a transcriptional activator that belongs to the WhiB family of transcriptional regulators conserved in actinomycetes (29,30). WhiB7 proteins have a variable N terminus and a conserved core sequence characterized by four iron-binding conserved cysteine residues, a G/Y-rich motif, and a positively charged AT-hook that binds an AT-rich region in DNA (31). whiB7 is induced in the presence of several structurally unrelated antibiotics, such as tetracycline, macrolides, and aminoglycosides, as well as compounds that perturb respiration, redox balance, and iron starvation (30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…WhiB7 proteins have a variable N terminus and a conserved core sequence characterized by four iron-binding conserved cysteine residues, a G/Y-rich motif, and a positively charged AT-hook that binds an AT-rich region in DNA (31). whiB7 is induced in the presence of several structurally unrelated antibiotics, such as tetracycline, macrolides, and aminoglycosides, as well as compounds that perturb respiration, redox balance, and iron starvation (30)(31)(32)(33)(34). A deletion of whiB7 in Mycobacterium smegmatis and Mycobacterium tuberculosis results in multidrug sensitivity (34).…”
mentioning
confidence: 99%